Phasing and climate forcing potential of the Millennium Eruption of Mt. Baekdu. ... - Lee, Giyoon; Burke, Andrea; Hutchison, William; Sugden, Patrick; Smith, Celeste; McConnell, Joseph R; Sigl, Michael; Oppenheimer, Clive; Rasmussen, Sune Olander; Steffensen, Jørgen Peder; Lee, Seung Ryeol; Ahn, Jinho (University of Bern, 2024)
The Millennium Eruption of Mt. Baekdu, one of the largest volcanic eruptions in the Common Era, initiated in late 946. It remains uncertain whether its two main compositional phases, rhyolite and trachyte, were expelled in a single eruption or in two. Investigations based on proximal and medial ash have not resolved this question, prompting us to turn to high-resolution ice-core evidence. Here, we report a suite of glaciochemical and tephra analyses of a Greenlandic ice core, identifying the transition from rhyolitic to trachytic tephra with corresponding spikes in insoluble particle fallout. By modeling annual snow accumulation, we estimate an interval of one to two months between these spikes, which approximates the hiatus between two eruptive phases. Additionally, negligible sulfur mass-independent fractionation, near-synchroneity between particle and sulfate deposition, and peak sulfur fallout in winter all indicate an ephemeral aerosol veil. These factors limited the climate forcing potential of the ...